Commerce with the universe : Africa, India, and the Afrasian imagination - Desai, Gaurav Gajanan (Columbia University Press, 2013)
Reading the life narratives and literary texts of South Asians writing in East Africa, Gaurav Desai builds a new history of Africa's encounter with slavery, colonialism, migration, nationalism, development, and globalization. Rather than approach literature and culture from a nation-centered perspective, Desai connects the medieval trade routes of the Islamicate empire, the early independence movements galvanized in part by Gandhi's southern African experiences, the invention of new ethnic nationalisms, and the rise of plural, multiethnic nations to the fertile exchange taking place across the Indian Ocean.